Carbon Gas Emissions (CO2 and CH4) in Coastal Community Settlement Area in The Mawasangka District - Central Buton, Indonesia - Rahman,; Hasidu, Laode Abdul Fajar; Asni,; Pieter Thomas Berhitu, (Malaysian Journal of Science (MJS), 2025)
Coastal communities build settlements on the sea in coastal areas. The resulting waste is disposed of in residential areas and undergoes decomposition, which triggers the release of carbon gas. This study aims to analyze carbon gas emissions that occur in residential areas. The gas extraction method uses a hood placed in a densely populated area (PP) and sparsely populated (JP). Gas concentration analysis used the gas chromatography (GC-MS) method. Analysis of differences in gas concentrations in the two regions was tested by ANOVA-single factor. The average concentration of CO2 gas in the two residential areas (PP and JP) was significantly different (P-value = 0.000067 <0.05), while the average concentration of CH4 gas was not significantly different (P-value = 0.1721 > 0.05). CO2 emissions in densely populated areas (PP) are 13.36 mg.m-2.h-1 and higher than sparsely populated areas (JP), which are 5.42 mg.m-2.h-1. These values ​​are significantly different (P-value = 0.00071 <0.05). Meanwhile, CH4 gas emissions in the PP area (0.036 mg.m-2.h-1) are greater than those in the JP area (0.014 mg.m-2.h-1). These values ​​are also significantly different (P-value = 0.03 <0.05). The PP area GWP value is 14.403 mg.CO2-eq m-2.h-1. This value is greater than the GWP value in the JP areas, which is 5.822 mg.CO2-eq.m-2.h-1. It Indicates that settlements in the coastal area of ​​Mawasangka Subdistrict make a significant contribution to increasing greenhouse gas emissions in the atmosphere, especially CO2 gas. Total greenhouse gas emissions and GWP from carbon gases must be controlled so they do not increase.